Robotic microfluidic imaging of blood stimulation- towards high-throughput portable measurement of haemostasis - Rüya Meltem Sarıyer; Kirandeep Gill; Sarah Helen Needs; Daniel Hodge; Nuno M. Reis; Chris Ian Jones; Alexander Daniel Edwards (British Journal of Pharmacy, 2023)
Measuring blood and platelet function is vital for the development and use of drugs that combat cardiovascular disease, such as anti-platelet drugs and other medicines that reduce the risk of thrombosis. We propose combining mass-produced microfluidic devices with open-source robotic instrumentation to enable development of affordable and portable, yet high-throughput and high-performance haematological testing. A time- and distance-resolved fluid flow analysis by Raspberry Pi imaging integrated with controlled sample addition and illumination, enables simultaneous tracking of capillary rise in 120 individual capillaries within 5 minutes. We showed that time-resolved microcapillary rise imaging permits blood function measurement by measuring thrombin-triggered activation of global haemostasis. Thrombin stimulation slowed vertical fluid velocity, consistent with a dynamic increase in viscosity. Microfluidic systems expand haematological testing towards high-efficiency, multi-parameter blood analysis necessary for understanding and improving cardiovascular health.